Cranial remains of an Eocene tarsier - Rossie, James B. (National Academy of Sciences, 2006)
The phylogenetic position of tarsiers relative to anthropoids and Paleogene omomyids remains a subject of lively debate that lies at the center of research into anthropoid origins. Omomyids have long been regarded as the nearest relatives of tarsiers, but a sister group relationship between anthropoids and tarsiers has also been proposed. These conflicting phylogenetic reconstructions rely heavily on comparisons of cranial anatomy, but until now, the fossil record of tarsiers has been limited to a single jaw and several isolated teeth. In this article, we describe cranial material of a fossil tarsiid from the middle-Eocene Shanghuang fissure-fillings in southern Jiangsu Province, China. This facial fragment, which is allocated to Tarsius eocaenus, is virtually identical to the corresponding anatomy in living tarsiers and differs substantially from that of early anthropoids such as Bahinia, Phenacopithecus, and Parapithecus. This new specimen indicates that tarsiers already possessed greatly enlarged orbits and a haplorhine oronasal configuration by the time they are first documented in the fossil record during the middle Eocene.